Complementary genetic screens identify the E3 ubiquitin ligase CBLC, as a modifier of PARP inhibitor sensitivity - Frankum, Jessica; Moudry, Pavel; Brough, Rachel; Hodny, Zdenek; Ashworth, Alan; Bartek, Jiri; Lord, Christopher J (Oncotarget, 2015)
Based on a series of basic, preclinical and clinical studies, the Poly (ADP-ribose) Polymerase 1 (PARP1) inhibitor, olaparib, has recently been approved for use in ovarian cancer patients with BRCA1 or BRCA2 mutations. By identifying novel predictive biomarkers of tumour cell sensitivity to olaparib, it is possible that the utility of PARP inhibitors could be extended beyond this patient subgroup. Many of the known genetic determinants of PARP inhibitor response have key roles in DNA damage response (DDR) pathways. Although protein ubiquitylation is known to play an important role in regulating the DDR, the exact mechanisms by which this occurs are not fully understood. Using two parallel RNA interference-based screening approaches, we identified the E3 ubiquitin ligase, CBLC, as a candidate biomarker of response to olaparib. We validated this observation by demonstrating that silencing of CBLC causes increased sensitivity to olaparib in breast cancer cell line models and that defective homologous recombination (HR) DNA repair is the likely cause. This data provides an example of how defects in the ubiquitin machinery have the potential to influence the response of tumour cells to PARP inhibitors.
Keywords: Poly(ADP-ribose) Polymerases; Proto-Oncogene Proteins c-cbl; rekombinace genetická; nádorové buněčné linie; signální transdukce; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; Breast Neoplasms; protoonkogenní proteiny c-cbl; ftalaziny; Recombination, Genetic; protein BRCA2; transfekce; RNA interference; Time Factors; regulace genové exprese u nádorů; poly(ADP-ribosa)polymerasy; ubikvitinace; Signal Transduction; posttranslační úpravy proteinů; RNA Interference; PARP inhibitory; Cell Line, Tumor; Ubiquitination; RNA interference screens; ubiquitin-proteasome system; Phthalazines; Poly(ADP-ribose) Polymerase Inhibitors; ženské pohlaví; Protein Processing, Post-Translational; CBLC; Humans; Gene Expression Regulation, Neoplastic; oprava DNA; Piperazines; časové faktory; viabilita buněk; Cell Survival; Transfection; BRCA2 Protein; DNA damage response; nádory prsu; PARP inhibitors; piperaziny; DNA Repair; Female; Poly (ADP-Ribose) Polymerase-1; poly(ADP-ribosa)polymerasa 1; lidé